PENGARUH PEMBELAJARAN DENGAN APLIKASI QUIZIZZ DAN MOTIVASI BELAJAR TERHADAP PENINGKATAN LITERASI MEMBACA SISWA SEKOLAH DASAR NEGERI 2 DONO ARUM SEPUTIH AGUNG: tesis - Widianto, Tri; Houtman; Juhana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effectiveness of Quizizz-based gamified instruction and students’ learning motivation in improving reading literacy among fifth-grade elementary students. Employing a quasi-experimental design, the research involved 46 students divided into an experimental group using Quizizz and a control group taught conventionally. Reading literacy tests were administered before and after the intervention, and motivation data were collected through a Likert-scale questionnaire measuring interest, attention, persistence, and participation. The findings reveal significant improvement in both groups, as indicated by paired sample t-test results. The experimental group achieved higher posttest performance, marked by an increase in minimum achievement and a higher maximum score, suggesting stronger overall learning consistency. Although the control group showed a higher numerical gain due to the ceiling effect, the independent sample t-test demonstrated a significant difference between the two groups, confirming the substantial influence of Quizizz on learning quality. High motivation scores, especially in interest and attention, further support the role of gamified learning in enhancing students’ affective engagement. The study concludes that Quizizz and learning motivation simultaneously contribute to improved reading literacy. The results emphasize the relevance of gamification as a strategic pedagogical tool for literacy instruction in the digital era.